2018
DOI: 10.3892/or.2018.6705
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 promotes angiogenesis of breast cancer

Abstract: Metastasis‑associated lung adenocarcinoma transcript 1 (MALAT1) is a long non‑coding RNA (lncRNA) that has an oncogenic role in some types of cancers, uncluding breast cancer (BC). To investigate the role of MALAT1 in human BC progression, we detected MALAT1 expression levels based on tissue samples from 20 BC cases and 20 healthy controls and found MALAT1 expression levels to be significantly high (P<0.05). Then, we knocked down endogenous MALAT1 in MCF‑7 cells using MALAT1 short hairpin RNA (shRNA). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 32 publications
5
35
1
1
Order By: Relevance
“…Each monomer contains two helix-loop-helix EF-hand-type motifs to bind Ca 2 + . [3][4][5][6][7][8] Therefore, atomic level in-depth characterization of the interaction between S100A4 andi ts target proteins is essential. It has gained increasinga ttention over recent decades because of its metastasis-promoting properties, as well as its role in the pathogenesis of rheumatoid arthritis and in fibrotic diseases.…”
mentioning
confidence: 99%
“…Each monomer contains two helix-loop-helix EF-hand-type motifs to bind Ca 2 + . [3][4][5][6][7][8] Therefore, atomic level in-depth characterization of the interaction between S100A4 andi ts target proteins is essential. It has gained increasinga ttention over recent decades because of its metastasis-promoting properties, as well as its role in the pathogenesis of rheumatoid arthritis and in fibrotic diseases.…”
mentioning
confidence: 99%
“…The long non-coding RNA MALAT1 has been demonstrated to regulate diverse cancer processes, including chemo-and radio-sensitivities (11,12). As a potential oncogenic lncRNA, MALAT1 was known to be upregulated in multiple cancers (13)(14)(15). This study reports the upregulation of MALAT1 in GC tissues and cells.…”
Section: Discussionmentioning
confidence: 81%
“…The MALAT1 is one of human tumor-related lncRNA that promotes the growth and metastasis of multiple cancers (11,12). Previous studies have demonstrated MALAT1 was frequently upregulated in human cancers by functioning as a potential oncogenic regulator in multiple cancers (13)(14)(15). However, the molecular targets of MALAT1 and detailed mechanisms are unclear.…”
mentioning
confidence: 99%
“…In the TNBC mouse model, direct intravenous injection of ASRPS reduced angiogenesis and tumor growth. Only a few studies have identified lncRNAs regulating angiogenesis in BC (Huang et al, 2018b; Zhang et al, 2017a), and no studies have investigated angiogenesis-regulating polypeptide encoded by lncRNA in BC. Our data suggested that ASRPS is a potent antitumor peptide through down-regulating tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%